Assessment of Perception and Perspective of Video Games on the Children: A Case Study of Tirana, Albania - Satka, Ermelinda; Troka, Pranvera (European Scientific Journal, ESJ, 2021)
Internet is a communication tool used in entertainment worldwide. The Internet is no longer a novelty for children and young people, but a necessity for them. For many children, today the distinction between online and daily activities is becoming smaller. Gradually, the computer game industry has become a lucrative business, increasing its production every day. The recent technology, depending on “PlayStation” slots, has begun to make significant impacts by creating a problem that needs to be addressed. On the other hand, there is little evidence that shows how social professionals are responding to new child protection challenges while navigating online. This paper focuses on describing, identifying, and assessing the perception and perspective of children aged 7-14 who are involved in playing computer games at PlayStation centers in Tirana. The method used in the study is qualitative research, which is specifically a case study research. The main instrument for data collection is the semi-structured interview with 20 children who are users of video games at PlayStation centers in the New Tirana neighborhood. The data analysis showed that children has a high attendance and dependence on computer games at PlayStation centers, leading to children’s positive perceptions and attitudes towards electronic games. Children’s attitudes towards playgrounds indicate the importance of these games in entertainment, leisure time, communication, and relationships with peers. It is important that everyone - parents and caretakers, teachers, institutions and government structures - should work together to create a safe environment for children regardless of where they are; at home, at school, or in public places such as internet centers.